A review on energy conscious designs of building façades in hot and humid climates: Lessons for (and from) Kuala Lumpur and Darwin. (February 2018) - Halawa, Edward; Ghaffarianhoseini, Amirhosein; Ghaffarianhoseini, Ali; Trombley, Jeremy; Hassan, Norhaslina; Baig, Mirza; Yusoff, Safiah Yusmah; Azzam Ismail, Muhammad
Abstract: Emerging environmental threats originating from rapid urbanization and the associated energy shortages, negative impacts of climate change, and sick building syndromes have led to government sectors and various construction-based professional bodies recognizing the need for developing effective sustainable building design strategies. As a result, growing interest in the development of effective solutions for enhancement of the sustainable energy performance of buildings has been observed in recent years. Along this line, building envelopes that separate the indoor from the outdoor environments, and in particular building façades, play a substantial role for energy saving in buildings. Nevertheless, this study argues that there is a lack of a systematic and comprehensive analysis of the available literature regarding the energy and thermal performance of building façades based on the various possible design and technical configurations, especially in hot and humid climates. Important decisions should be made by architects and engineers during the early design stages of buildings with viewpoints to the ultimate impacts of building physics on the overall energy performance and indoor comfort conditions of buildings. With such a research gap in existing literature, in these early stages many key façade attributes may be overlooked. Hence, this study attempts to develop a state-of-the-art analysis of the existing literature about the circumstances of optimizing the performance of building façades, particularly in hot and humid climates. Likewise, the study extracts practical lessons learned from AEC industry and demonstrates the current status of utilizing energy efficient building façades in recent construction developments in Malaysia (Kuala Lumpur) and Australia (Darwin). Finally, the study draws attention to the emerging innovative solutions for the design of building façades towards improving the energy efficiency of building sector and contributing to the sustainable development of cities.